Morgan Swift and the trail of the jaguar - Lesley, Martine (New York : Random House, 1985)
A Christmas vacation in Mexico with two of her students becomes a working holiday for Morgan Swift when her talents are needed on an archaelogical dig that promises to yield exciting new information on the Mayan civilization.
Keywords: Indians of Mexico -- Fiction; Mayas -- Fiction; Archaeology -- Fiction; Adventure and adventurers -- Fiction; Children$1 (Bs stories Americans; Mexico -- Fiction